A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF MAN 2 MODEL PEKANBARU IN COMPREHENDING HORTATORY EXPOSITION TEXT - Muthia Abrar; Eliwarti Eliwarti; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This descriptive research aims to find out the ability of the second year students of MAN 2 Model Pekanbaru in comprehending hortatory exposition text. The population of this research were the second year students of MAN 2 Model Pekanbaru in academic year 2016/2017. The number of sample were 50 students which were chosen by using random sampling technique. The data were collected using reading comprehension test in multiple choice types by giving 5 hortatory exposition texts with 40 multiple choice items.The results of the data analysis showed that the mean score of the students’ ability in comprehending hortatory eksposition text is as big as 65.55. It can be concluded that the ability of the second year students of MAN 2 Model Pekanbaru in comprehending hortatory eksposition text is categorized good. Based on the result of the students’ ability in each of reading comprehension component, the lowest component of reading comprehension for the students was finding meaning of certain words (54.8) and the highest one was finding factual information (82). This result suggests that the students need to learn more in comprehending hortatory exposition text. Even though the mean score is classified in good level, but only few of students pass the minimum passing rate of their school.Keywords: Study, Ability, Hortatory Exposition Text.